Blanded Learning: Peningkatkan Motivasi Guru Rumpun PAI dalam Melaksanakan Pembelajaran Jarak Jauh di MA Sunan Pandan Aran - Ida Uswatun Hasanah (Pusat Pengembangan Madrasah (PPM), dan Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2022)
This study aims to increase the motivation of PAI teachers at MA Sunan Pandan Aran in carrying out distance learning in 2021/2022 through blanded learning by utilizing classroom whatsapp. This research is a surveillance action research. Each cycle consists of stages of planning, action, observation and reflection. Actions in cycle 1 and cycle 2 use actions in the form of blanded learning. Data is obtained through direct observation when teachers carry out blanded learning. Descriptive analysis is presented in tabular form to make it easier to understand the research results presented. The results showed that the implementation of blanded learning through whatsapp classes can increase teacher motivation to carry out distance learning. The implementation of blanded learning in cycle 1 showed an increase in the motivation of pai teachers by 42.8% with high motivation, while the other 57.2% were still in the category of sufficient motivation. In the second cycle, it showed an increase in the motivation of PAI teachers in MA Sunan Pandan Aran by 85.7% with high motivation, while the other 14.3% was still in the category of sufficient motivation. This success is in accordance with the success criteria, namely the blanded learning model is said to be successful if 85% of pai MA Sunan Pandan Aran teachers show high motivation in carrying out long-distance learning.